Carcass Production and Meat Tenderness Characteristics of Culled Quail Fed with Azolla microphylla Flour Supplemented Basal Feed - Elly Tugiyanti; Soegeng Herijanto (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The aim of this research was to understand the effect of Azolla microphylla flour supplementation in the basal feed on carcass production and meat tenderness characteristics of culled quail. The materials used in this research were 100 culled quails at 48-week-old age and commercial quail feed. The research was conducted as an experimental research and used Completely Randomized Design. Four treatments were done in this research, which was basal feed without Azolla microphylla flour supplementation; basal feed supplemented with 1% Azolla microphylla flour; basal feed supplemented with 2% Azolla microphylla flour, and basal feed supplemented with 3% Azolla microphylla flour. Each treatment was done 4 times with each fed into 5 quails. The observed variables include carcass production (carcass percentage, breast meat percentage, thigh meat percentage, back meat percentage, and wing meat percentage) and meat tenderness characteristics (meat fat content, collagen content, pH and meat tenderness). The obtained data were then analyzed by analysis of variance and if the result showed a significant effect, further analysis will be done by honestly significant difference test. The analysis of variance showed that Azolla microphylla flour supplementation showed significant effect (P<0.05) on the carcass percentage, breast meat percentage, meat fat content, collagen content, and meat tenderness but showed no significant effect (P>0.05) on the thigh meat percentage, back meat percentage, wings meat percentage and meat pH. The research concluded that Azolla microphylla flour supplementation in the basal feed will increase carcass production and meat tenderness of culled quail meat at maximum 2% of supplementation level.